2021
DOI: 10.1080/09658416.2021.1965153
|View full text |Cite
|
Sign up to set email alerts
|

‘I like my accent but…’: EFL teachers’ evaluation of English accent varieties

Abstract: The instrument for quantitative data collection 1. Personal information (1) Age _______________ (2) Sex (F)______ (M)_______ (Prefer not to state)_______ (3) The workplace (State)__________(Private)___________(Other)____________Please state it. (4) What grade/level do you teach English to? _____________________________________ (5) Have you lived in an English-speaking country? (Yes)_________ (No)__________ a. If yes, where? __________________ b. For how long?_______________ (6) Do you speak other languages? (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Using MGT and VGT, respectively, He and Zhang (2010) and Chan (2016) surveyed Chinese teachers' and students' attitudes toward English accent varieties and reported that teachers and students considered NS‐based norms and models the most desirable in China's English classroom. Finally, Mısır and Gürbüz (2021) surveyed Turkish teachers' attitudes toward English accent varieties using VGT and found that teachers rated the standard English accents more favorably as the teaching model and that they attached more prestige to these accents. Considering the so‐called “standard varieties of English” (i.e., GA or RP) as the only varieties worth learning by teachers in many parts of the world would strengthen the fallacy of native and nonnative distinction and also give rise to the notion that non‐native teachers of English are inferior to those considered native (Jenkins, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using MGT and VGT, respectively, He and Zhang (2010) and Chan (2016) surveyed Chinese teachers' and students' attitudes toward English accent varieties and reported that teachers and students considered NS‐based norms and models the most desirable in China's English classroom. Finally, Mısır and Gürbüz (2021) surveyed Turkish teachers' attitudes toward English accent varieties using VGT and found that teachers rated the standard English accents more favorably as the teaching model and that they attached more prestige to these accents. Considering the so‐called “standard varieties of English” (i.e., GA or RP) as the only varieties worth learning by teachers in many parts of the world would strengthen the fallacy of native and nonnative distinction and also give rise to the notion that non‐native teachers of English are inferior to those considered native (Jenkins, 2006).…”
Section: Introductionmentioning
confidence: 99%